Capsular polysaccharides facilitate enhanced iron acquisition by the colonial cyanobacterium Microcystis sp. isolated from a freshwater lake. Issue 1 (11th January 2016) - Li, Zheng‐Ke; Dai, Guo‐Zheng; Juneau, Philippe; Qiu, Bao‐Sheng
Abstract : Microcystis sp., especially in its colonial form, is a common dominant species during cyanobacterial blooms in many iron‐deficient water bodies. It is still not entirely clear, however, how the colonial forms of Microcystis acclimate to iron‐deficient habitats, and the responses of unicellular and colonial forms to iron‐replete and iron‐deficient conditions were examined here. Growth rates and levels of photosynthetic pigments declined to a greater extent in cultures of unicellular Microcystis than in cultures of the colonial form in response to decreasing iron concentrations, resulting in the impaired photosynthetic performance of unicellular Microcystis as compared to colonial forms as measured by variable fluorescence and photosynthetic oxygen evolution. These results indicate that the light‐harvesting ability and photosynthetic capacity of colonial Microcystis was less affected by iron deficiency than the unicellular form. The carotenoid contents and nonphotochemical quenching of colonial Microcystis were less reduced than those of the unicellular form under decreasing iron concentrations, indicating that the colonial morphology enhanced photoprotection and acclimation to iron‐deficient conditions. Furthermore, large amounts of iron were detected in the capsular polysaccharides (CPS) of the colonies, and more iron was found to be attached to the colonial Microcystis CPS under decreasing iron conditions as compared to unicellular cultures. These results demonstrated that colonial Microcystis can acclimate to iron deficiencies better than the unicellular form, and that CPS plays an important role in their acclimation advantage in iron‐deficient waters.